Determination of Alpha-and Beta-cryptoxanthins, and Alpa-and Beta Carotenes in Buah Merah Oil By HPLC-UV Detection - Wada, Mitsuhiro; Fujimoto, Kaori; Nishigaki, Toshiaki; Febriyanti, Erna; Ikeda, Rie; Nakashima, Kenichiro (Balai Besar Industri Agro, 2013)
A high-performance liquid chromatography-UV detection method for determination of Alpha-and Beta-cryptoxanthins and, Alpha-and Beta-carotenes in Buah Merah oil was developed. The separation of the four carotenoids was achieved by a combination of a Handy ODS column (150x4.6 mm, i.d.) and a Develosil Combi-RP-5 (50x4.6 mm, i.d.) via a 3-port switching valve. The mobile phase used was a mixture of CH3CN/CH3OH/ethyl acetate (=68:23:9, v/v/v). The retention times of Alpha-and Beta-cryptoxanthins and, Alpha and Beta-carotenes were 18, 20 53 and 60 min, respectively. The clean-up of Buah Merah oil was performed by liquid-liquid extraction after saponification with 13.5 M KOH solution. The calibration curves of the carotenoids showed good linearity (r> 0.000. The detection limits of four carotenoids at a signal-to noise of 3 were from 0.36 to1.14 ng/mg. Furthermore, the proposed method could be successfully applied to determine the carotenoids in 10 Buah Merah oil samples.Â